2012
DOI: 10.3109/00952990.2012.694527
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Etiology of Substance Use among American Indians and Alaska Natives: Risk, Protection, and Implications for Prevention

Abstract: Background The epidemiology and etiology of substance use and disorder in American Indian and Alaska Native (AI/AN) communities have received increasing attention over the past 25 years and accumulating evidence provides important insights into substance use patterns in these populations. Objectives and methods We provide a descriptive sketch of the AI/AN population in the United States today, present a brief review of the literature on the epidemiology and etiology of substance use within these populations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
169
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(174 citation statements)
references
References 66 publications
5
169
0
Order By: Relevance
“…To date, research has been relatively limited regarding smoking characteristics among the 562 federally recognized tribes in the U.S. However, studies conducted thus far have revealed higher smoking rates among Northern Plains tribes in history (i.e., forced removal from Native lands, coerced placement into boarding schools, and laws prohibiting Indigenous spiritual practices; Walters et al, 2002;Duran and Duran, 1995;Whitesell et al, 2012). According to this theory, the effects of historically based traumas have been inter-generational, meaning these influences have had ongoing deleterious effects on the health and well-being of this population, including significant substance use and smoking, high suicide rates, and lower levels of family cohesion (Wiechelt et al, 2012;Brave Heart et al, 2011;Walters et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…To date, research has been relatively limited regarding smoking characteristics among the 562 federally recognized tribes in the U.S. However, studies conducted thus far have revealed higher smoking rates among Northern Plains tribes in history (i.e., forced removal from Native lands, coerced placement into boarding schools, and laws prohibiting Indigenous spiritual practices; Walters et al, 2002;Duran and Duran, 1995;Whitesell et al, 2012). According to this theory, the effects of historically based traumas have been inter-generational, meaning these influences have had ongoing deleterious effects on the health and well-being of this population, including significant substance use and smoking, high suicide rates, and lower levels of family cohesion (Wiechelt et al, 2012;Brave Heart et al, 2011;Walters et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…NA girls are at increased risk for trauma exposure during childhood (Ehlers & Gizer, 2013;Yuan et al, 2006), which increases later risk for substance use (Whitesell et al, 2012). Discrimination and historical loss are two important risk factors for alcohol abuse among NA women (Whitbeck et al, 2004).…”
Section: T His Study Provides New Information Tomentioning
confidence: 99%
“…Correlations among each construct at each time point were expected. Given the reports of NA girls' greater exposure to social risks (Ehlers & Gizer, 2013;Friese et al, 2015;Whitesell et al, 2012;Yuan et al, 2006), we hypothesized that NA young women would have exposure to higher levels of social risks that would result in higher individual-level risks. However, we hypothesized similar effects of the risk and protective factors on alcohol use among NA and non-Native young women.…”
Section: T His Study Provides New Information Tomentioning
confidence: 99%
See 1 more Smart Citation
“…11 These programs have proven benefits at both the individual and societal levels, including reductions in use of injection drugs, acquisition and transmission of viral hepatitis and HIV, death, crime rates, and improvements in participants' overall quality of life. 11,12 In Canada, 13 the United States 14 and Australia, 15 rates of opioid dependence tend to be higher in Aboriginal than in non-Aboriginal communities, as are the rates of associated harms and death. 16 However, the beneficial effects of methadone programs are similar among both Aboriginal and non-Aboriginal participants.…”
mentioning
confidence: 99%